The art of a corporation - Howes, Jennifer, author.
1 online resource (xv, 218 pages)
Keywords: "The Art of a Corporation is a comprehensive study of artworks that were commissioned and collected by the East India Company from the early 17th to the mid-19th century. These items range from oil paintings on canvas and marble statuary, to sandstone Buddhas and metal figurines of Hindu deities. The book takes a chronological approach and focuses on provenance to show that objects are valuable primary resources for understanding the East India Company's history. The artworks illustrate how one of the longest surviving multinational corporations in the western world changed over its three-century history and provide a powerful visual account of its perpetually reinvented image. This book is a must read for scholars and researchers of art history, colonial art, colonial studies, British history, economic history, business history, South Asian history, post-colonial studies and cultural studies"--